Seleção de genótipos, manejo e perfil químico de aroeira (Schinus terebinthifolius Raddi.) no Estado do Espírito Santo. - Ruas, Fabiana Gomes (2016)
The research was developed in the northern region of the Espírito Santo State with the support of Biomes-Atlantic Forest Project, under field conditions, in an experimental area located at Fazenda São Marcos Linhares-ES (19 ° 12'58.5 "S, 40 ° 03'09.6 '' W). The objective was to select, fertilizer and pruning management and characterize genotypes of aroeira (Schinus terebinthifolius) with potential in the production of fruits and bioactive products for value addition in family farming. Heterogeneous populations of aroeira grown in two experimental areas were evaluated. In area 1 (spodosoil) was evaluated the stress abiotic and in area 2 (argisoil), the management with six types of fertilizers and two pruning methods (pruning branches-PR and pruning drastic-PD), determining the development (diameter at the base of stem-DAC, plant height and crown area), post-pruning branch growth, reproductive phenology (floral biology), yield and, fruit quality regarding the chemical profile of fruit and leaves. The chemical profile of the fruits was carried out by thin layer chromatography analysis (TLC) and, Mass Spectrometry and Gas Chromatography coupled to Mass Spectrometry (GC-MS). A total of 100 genotypes were selected. In the plants selected twelve were considered elite in the fruit yield, and five were considered excellent for achieving average production 30% above the plant production average obtained in 2014 and 2015. Climatic factors (excess of water in 2013 and severe drought in 2014 and 2015) and the genetic variability of the species were associated in the analyzed characteristics. Only one genotype was resistant to water stress. Among the 882 plants evaluated in the area 2, in 2014, 2015 and 2016, near half consisted of plants with male flowers (staminate), the other half by plants with female flowers, and only two plants with hermaphrodite flowers. The selected genotypes are being cloned to enrich the Active Germplasm Bank of Aroeira, at the Incaper Experimental Farm of Jucuruaba, in the municipality of Viana-ES. According to dendrometric variables and branch growth, the aroeira responded well to fertilization in terms of development of plants, six months after pruning. The fertilization influenced the fruit production in 2014, with a statistic significant difference (P <0.05), and with higher production in the treatment two (NPK). In 2015, there was no significant difference between the fertilization treatments. Pruning of branches was a strategy that should be recommended as practice for producers of aroeira. Phytochemical studies showed constant presence of sesquiterpenes (higher in fruits), cardanoids and triterpenes (higher in leaves). Considering these chemical groups, samples from different treatments of fertilizers were not statistically different (P<0.05). The plant selection with high production is the initial step to provide genetic material of certified quality for farmers.